2022
DOI: 10.1002/mar.21714
|View full text |Cite
|
Sign up to set email alerts
|

Buying happiness: How brand engagement in self‐concept affects purchase happiness

Abstract: In general, experiential purchases have been found to make people happier than material purchases. However, previous research has ignored a crucial issue-the importance of the brand and the consumer−brand relationship in this context. Since many purchases are associated with a brand and the brand is often the main motivation for the purchase, we argue that researchers should include the consumer −brand relationship in studies on the effects of material versus experiential consumption on happiness. Building on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…What is more, Goodman et al (2016) observed that in the context of important life milestones, such as graduations or promotions, it is material, and not experiential, purchases that have a happiness edge. Further illustrating the tentative nature of the experience recommendation, a recent study from Razmus and colleagues (2022), found no differences in purchase‐related happiness across purchase types for consumers who generally treat brands as important elements of their self‐schemas. Similarly, Lee et al (2022) demonstrate that when material purchases are imbued with human‐like characteristics they offer similar levels of happiness as experiential purchases.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…What is more, Goodman et al (2016) observed that in the context of important life milestones, such as graduations or promotions, it is material, and not experiential, purchases that have a happiness edge. Further illustrating the tentative nature of the experience recommendation, a recent study from Razmus and colleagues (2022), found no differences in purchase‐related happiness across purchase types for consumers who generally treat brands as important elements of their self‐schemas. Similarly, Lee et al (2022) demonstrate that when material purchases are imbued with human‐like characteristics they offer similar levels of happiness as experiential purchases.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The general consensus from this research stream is that consumers tend to derive greater satisfaction and happiness from experiential consumption than from material possessions (Caprariello & Reis, 2013;Carter & Gilovich, 2010, 2012Howell & Hill, 2009;Kumar et al, 2014;Nicolao et al, 2009;Razmus et al, 2022;Weingarten & Goodman, 2021). The greater positive impact that experiential purchases have on one's happiness has been termed the experiential advantage (Gilovich & Gallo, 2020;Weingarten & Goodman, 2021).…”
Section: Experiential Purchases and The Experiential Advantagementioning
confidence: 99%
“…An extensive body of work compares experiential and material purchases and their impact on consumer well‐being, including satisfaction (Carter & Gilovich, 2010), regret (Rosenzweig & Gilovich, 2012), intrinsic (vs. extrinsic) motivation (Ho & Wyer, 2021), and happiness (Van Boven & Gilovich, 2003; Weingarten & Goodman, 2021). The general consensus from this research stream is that consumers tend to derive greater satisfaction and happiness from experiential consumption than from material possessions (Caprariello & Reis, 2013; Carter & Gilovich, 2010, 2012; Howell & Hill, 2009; Kumar et al, 2014; Nicolao et al, 2009; Razmus et al, 2022; Weingarten & Goodman, 2021). The greater positive impact that experiential purchases have on one's happiness has been termed the experiential advantage (Gilovich & Gallo, 2020; Weingarten & Goodman, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The concept of CBRs is centered on the notion that the bond between a consumer and a brand is analogous to that of interpersonal relationships (Fournier, 1998). Specifically, this study stream has focused on the building of a strong brand relationship as a long‐term strategy and outcome for the brand, and various studies have shown that this is built on the basis of positive brand behavior leading to positive consumer evaluations (MacInnis & Folkes, 2017; Park & John, 2018; Razmus et al, 2022). The long‐term relational focus has also shown to provide a better method of predicting buying behavior (Nyffenegger et al, 2015; Sarkar et al, 2021).…”
Section: Research Background and Hypothesesmentioning
confidence: 99%